Nonlinear vibration of wire-wrapped fuel rod subjected to axial flow - Yu Zhang; Pengzhou Li (Alexandria Engineering Journal)
Wire-wrapped fuel rods are widely utilized in lead-bismuth reactors and subjected to high kinetic energy fluid flow, significantly influencing the reactor's safe operation. This study addresses the increasing interest in fuel assemblies by developing a theoretical fluid-structure interaction model to elucidate the dynamic behavior of wire-wrapped fuel rods. Newton's law is employed to derive the governing equation, with fluid force coefficients determined through widely accepted numerical simulations, while the impact and downstream nonlinear boundary condition are incorporated. Two comparative analyses robustly validate the reliability of the proposed model. Building on this model, the study investigates the nonlinear vibration characteristics (amplitude, phase space, impact forces, etc.) of the structure, considering the effects of gap size and streamlining parameter. Moreover, the theoretical derivation of this model provides a foundational and dependable mathematical framework to facilitate further research on fretting wear.